The Validity and Reliability of Parent’s Recall for Routine Immunization in Cameroon - Yakum, Martin Ndinakie; Ajong, Atem Bethel; Funwie, Atanga Desmond; Shah, Zahir (Archives of Clinical and Biomedical Research, 2023)
Introduction: In the absence of immunization documentations, parent’s recall is used to assess children immunization status. During the 2018 demographic and health survey in Cameroon, parent’s recall was the only source of information for 47% of children assessed for immunization coverage. The objective of this study was to determine the validity of parent’s recall for immunization using the vaccination card as the reference in Yaoundé-Cameroon. Methods: The study targeting parents of children aged 0-59months who had their children’s vaccination cards. The immunization history of each child was taken based on both parent’s recall and vaccination card. Using the vaccination card as a reference, the sensitivity, specificity, positive predictive value, and negative predictive value of parent’s recall were calculated. The degree of agreement and the kappa statistics between the two methods were calculated using R version 4.1.0 (2021-05-18). Results: A total of 529 households were visited and 87 eligible parents enrolled. Approximately 55.2% of the children were girls and 53% of them were aged 12-59 months. In total, 94.25% of the participants enrolled were one of the biological parents of the children, with mothers making the majority 86.20% of participants. When combined for all vaccines in the EPI (i.e. one dose BCG, 4 doses of OPV, 3 doses of pentavalent vaccine, 3 doses of PCV-13, 2 doses of rotavirus vaccine, one dose of measles/rubella vaccine and one dose of the yellow fever vaccine), the sensitivity, specificity, positive predictive value, and negative predictive value of parent’s recall were 63%, 60%, 90%, and 23% respectively. The degree of agreement between the two sources was highest for BCG (94%) and lowest with Polio2 (32%). Parent’s recall (94%) was most likely to correctly predict BCG vaccination status of a child than using the scars on the forearm (74%). Conclusion: Our conclusion is that validity and reliability of parent’s recall vary a lot across different vaccines and parent’s recall is not very reliable for immunization status assessment in children. Parent’s recall is preferred for verifying BCG immunization to scars on the forearm. In general, we recommend that parent’s recall for routine immunization should be used only as a last resort or for BCG, and measles and Yellow Fever vaccines.